THE APPLICATION OF SUSTAINABLE INNOVATIONS WITHIN BUSINESS OPERATIONS: THE CASE OF NGEBUTS ELECTRIC BIKES - Dzulfikar Ahmad Furqon (Jurnal TAMBORA, 2023)
This paper explores NGEBUTS electric motorbikes and examines how their manufacturers exemplify a sustainable innovation approach in their business operations. The study applies a five-stage sustainability mapping framework to understand NGEBUTS's emergence in the Indonesian EV market and their use of sustainable innovation. The findings highlight the importance of incorporating sustainability into business models, products, technologies, and processes to enhance competitiveness. The research reveals that sustainability initiatives can reduce operational costs and increase revenues, benefiting both the bottom line and the top line. NGEBUTS demonstrates how they seize innovation opportunities, leverage regulations, and apply circular economy techniques to create a sustainable business model. Additionally, the paper discusses the potential of Indonesia's natural resources for renewable energy and job creation. While the study acknowledges the limitations of measuring long-term success, it concludes that NGEBUTS's vision, innovative ideas, and utilization of local resources position them as a leading example for companies to prioritize social and environmental factors to thrive in the current competitive landscape.